Users' views on cultural ecosystem services of urban parks: An importance-performance analysis of a case in Beijing, China. (March 2022) - Gai, Shijie; Fu, Jiaming; Rong, Xiao; Dai, Linlin
Abstract: Rapid urbanisation and global climate change have had a profound impact on the development of cities. Nature-based solutions, such as urban parks in dense city areas, play an important role in addressing such problems. They provide cultural ecosystem services to improve human well-being. Scholars have studied the cultural ecosystem services provided by urban parks from the perspective of users. Insufficient research, however, has addressed differences in perceptions of cultural ecosystem services among different social groups, as well as the relationship between the supply and demand of cultural ecosystem services. In this study, based on face-to-face questionnaire surveys and interviews, we analysed users' perceptions of cultural ecosystem services in an urban park in Wudaokou, a multifunctional area in the centre of Beijing, China. The study pioneers the application of importance–performance analysis, a method to systematically analyse users' perceptions of the importance and performance of the cultural ecosystem services of urban parks. We found significant differences in perceptions of importance, and the importance scores overall were significantly higher than the performance scores. Users' perceptions of performance were affected by spatial identity source attribute and age: residents living nearby appreciated the performance more than commuters and passers-by; young people gave the highest scores. The importance–performance analysis approach offers a mechanism to help policymakers and planners match peoples' needs with cultural ecosystem service provision.